The Effect of Hyaluronic Acid on MMP-9 Expression in Trabecular Meshwork Cell Culture of Patient with Primary Open Angle Glaucoma - Cicih Komariah; Ma’sum Effendi; Hidayat Sujuti (Faculty of Medicine, University of Jember, 2017)
In primary open angle glaucoma, decrease of hyaluronic acid level is related to extracellular matrix deposition of trabecular meshwork. Extracellular matrix deposition will increase humor aqueous outflow resistance which in turn increase the intraocular pressure. MMP-9 as one of matrix metalloproteinase (MMP) family, has a high potency to degrade the extracellular matrix. The expression of MMP-9 can be activated by hyaluronic acid through its binding with CD44 as hyaluronic main receptor. The aim of this research is to determine the effect of hyaluronic acid on MMP-9 expression in trabecular meshwork cell culture of patient with primary open angle glaucoma by immunocytochemical method. Trabecular meshwork cell culture were exposed to hyaluronic acid at four different concentration (0mg/ml, 1 mg/mL, 3 mg/mL, 6 mg/mL). After 24 hours incubated, we find a significant difference of MMP-9 expression between control group and group with hyaluronic acid. There was significant correlation between hyaluronic acid and MMP-9 expression. Hyaluronic acid exposure will increase MMP-9 expression in trabecular meshwork cell culture. This finding suggest that hyaluronic acid can influence the resistance of humor aqueous outflow in trabecular meshwork by up-regulating MMP-9 expression, and therefore will increase extracellular matrix degradation.Key words : hyaluronic acid, primary open angle glaucoma, MMP-9